2020
DOI: 10.1108/jgoss-02-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Service outsourcing decisions – a process framework

Abstract: Purpose The purpose of this paper is to compare service outsourcing decisions between public and private organizations and against a theoretical decision-making framework to both understand differences across the sectors and to provide an outsourcing framework more suitable specifically for outsourcing (and for the public sector). Design/methodology/approach Multiple case studies, i.e. a study of phenomena (here outsourcing process) at various sites is used as an approach. Findings Findings indicate that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
1
19
0
1
Order By: Relevance
“…Lonsdale (1999) argues that firms achieve poor outsourcing results because managers fail to consider its risks and develop safeguards. Recent articles propose holistic decision processes including different criteria (Lee et al, 2012;Taponen and Kauppi, 2020). Rehme et al (2013) present several frameworks for outsourcing decisions, while Gunasekaran et al (2015) discuss the use of performance measures and metrics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Lonsdale (1999) argues that firms achieve poor outsourcing results because managers fail to consider its risks and develop safeguards. Recent articles propose holistic decision processes including different criteria (Lee et al, 2012;Taponen and Kauppi, 2020). Rehme et al (2013) present several frameworks for outsourcing decisions, while Gunasekaran et al (2015) discuss the use of performance measures and metrics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through outsourcing, organizations expect to obtain several benefits: reduced costs, focus on core competences, access to more advanced technologies. However, there are significant risks that may materialize if outsourcing is not successful (Harland et al, 2005;Kremic et al, 2006;Giosa and Morales, 2017;Taponen and Kauppi, 2020). Problems such as sacrificed service quality, accountability issues, poor service coordination, reduced flexibility and information leakages have been raised by both private and public sector organizations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This challenge that emanates as a result of lack of internal expertise to handle IT activities (software development) amongst decision-makers, IT practitioners, and heads of departments in the public sector is gradually becoming thing of the past as outsourcing activities continue to come into play (4). No doubt recent studies also indicated outsourcing activities in the public sector is highly beneficial for decision-makers, IT practitioners, and heads of departments as it allows them to fully concentrate on their assigned professional activities rather than wasting time on activities that are unrelated to their expertise which may invariably affect their stipulated strategic objectives (5,6). However, researches have proven the challenge still faced by IT practitioners who could not avoid selecting the wrong IT provider during the outsourcing selection process due to uncertain situations faced in human perceptions or assessment in decision making (7,8,9).…”
Section: Introductionmentioning
confidence: 99%